Importance of Pre-treatment Fractional Anisotropy Value in Predicting Volumetric Response in Patients with Meningioma Treated with Gamma Knife Radiosurgery. - ÇEŞME, DİLEK HACER; Cesme, Dilek Hacer; ALKAN, ALPAY; Alkan, Alpay; SEYİTHANOĞLU, MEHMET HAKAN; Sari, Lutfullah; HATİBOĞLU, MUSTAFA AZİZ; Yabul, Fatma; Temur, Hafize Otcu; Aykan, Mahmut Esat; Hatiboglu, Mustafa Aziz; Seyithanoglu, Mehmet Hakan (My University, 2021)
Background: The importance of pre-treatment Diffusion Tensor Imaging (DTI) parameters in determining the response to treatment after radiosurgery in patients with meningioma has not yet been clearly revealed. Objective: This study was conducted to determine tumor volume changes in terms of radiological response in patients with meningioma treated with Gamma Knife Radiosurgery (GKR) and to analyze the relationship between Total Tumor Volume (TTV) and Diffusion Tensor Imaging (DTI) parameters. In addition, we investigated whether the response to treatment can be predicted by pre-radiosurgery DTI findings. Methods: Fifty-four patients were assessed using MRI and DTI before and after GKR. Mean Diffusivity (MD), Fractional Anisotropy (FA), Radial Diffusivity (RD), and TTV of tumour were determined. Patients with 10% or more decrease in TTV after GKR were classified as group 1 and those with less than 10% decrease in volume or increase in volume were considered group 2. The relationships between MD, RD, and FA values and TTV were investigated. Results: A decrease of 46.34% in TTV was detected in group 1 after GKR, while TTV increased by 42.91% in group 2. The lowest pre-treatment FA value was detected in group 1. In addition, after GKR, FA values showed a significant increase in group 1. MD and RD values increased in both groups after radiosurgery. There was a negative correlation between pre-treatment FA, RD, and MD values after radiosurgery. Conclusion: Detection of low FA values due to the poor fiber content in meningioma before radiosurgery may be a guide in predicting the response to treatment. Further studies are required to have a better understanding of the relationship between pre- and post-treatment follow-up FA values and tumor volume in determining the efficacy of GKR in patients with meningioma.
Keywords: Diffusion tensor imaging; Gamma knife radiosurgery; Fractional anisotropy; Mean diffusivity; Meningioma; Radiosurgery; Tumor volume